Internal Communication in the Eighth Circuit Court of Appeals - Stephen L. Wasby (Washington University Law Quarterly, 1980)
This Article, part of a study of intracircuit communication and consistency within the United States Courts of Appeals for the Eighth and Ninth Circuits, focuses on the Eighth Circuit's appellate judges' communication with each other, district judges, and judges from outside the circuit. The Article concludes with specific attention to the effects on communication caused by geography and the number of judges on the court.
Keywords: Judicial process; United States. Court of Appeals for the 8th Circuit; United States